2018
DOI: 10.1186/s12964-018-0293-3
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-dependent and independent actions of P2X7 in regulation of mitochondrial and lysosomal functions in microglia

Abstract: BackgroundP2X7 is ubiquitously expressed in myeloid cells and regulates the pathophysiology of inflammatory diseases. Since mitochondrial function in microglia is highly associated with microglial functions in controlling neuronal plasticity and brain homeostasis, we interested to explore the roles of P2X7 in mitochondrial and lysosomal functions as well as mitophagy in microglia.MethodsP2X7−/− bone marrow-derived macrophages (BMDM), primary microglia and BV-2 immortalized microglial cells were used to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 67 publications
3
49
1
Order By: Relevance
“…Previously, the involvement of P2X7R in modulation of AMPK activity and regulation of autophagic flux was highlighted. It was documented that AMPK is a key signalling modulator of P2X7R to induce mitophagy and mitochondrial fission in microglia [113] and that the deleterious effect of P2X7R predominantly include lysosomal impairment in microglial cells [113,114]. Conversely, in our study, we demonstrated that α-Syn-dependent stimulation of P2X7R in neuronal cells results in inhibition of AMPK activity, followed by the inhibition of Ulk-1, which might have the negative effect on autophagy initiation.…”
Section: Discussionsupporting
confidence: 43%
“…Previously, the involvement of P2X7R in modulation of AMPK activity and regulation of autophagic flux was highlighted. It was documented that AMPK is a key signalling modulator of P2X7R to induce mitophagy and mitochondrial fission in microglia [113] and that the deleterious effect of P2X7R predominantly include lysosomal impairment in microglial cells [113,114]. Conversely, in our study, we demonstrated that α-Syn-dependent stimulation of P2X7R in neuronal cells results in inhibition of AMPK activity, followed by the inhibition of Ulk-1, which might have the negative effect on autophagy initiation.…”
Section: Discussionsupporting
confidence: 43%
“…Activation of the P2X7 receptor by its agonist, BzATP, led to ROS‐ and CaMKK‐dependent AMPK activation, disruption of mitochondrial dynamics, autophagy, and lysosomal biogenesis followed by partial cell death. The cytotoxicity was also a result of P2X7‐mediated mitophagy and cathepsin B activation in microglial cells . Moreover, the loss of activity of 2 mitophagy regulators, Parkin or PINK1, is directly linked with microglial NLRP3 activation in PD .…”
Section: Nlrp3 Inflammasome‐mediated Inflammatory Pathways In Pdmentioning
confidence: 99%
“…The cytotoxicity was also a result of P2X7-mediated mitophagy and cathepsin B activation in microglial cells. 74 Moreover, the loss of activity of 2 mitophagy regulators, Parkin or PINK1, is directly linked with microglial NLRP3 activation in PD. 75,76 In bone marrow-derived macrophage (BMDM), activation of the AIM2 and NLRP3 inflammasomes has been found to trigger caspase-1-dependent mitochondrial damage through attenuation of mitophagy.…”
Section: Mitochondrial Dysfunction and Mitophagymentioning
confidence: 99%
“…Numerous studies have indicated the involvement role of P2X7R in autophagy regulation [32,33]. Shortterm P2X7R activation has been shown to stimulate autophagic ux, while persistent P2X7R stimulation leads to autophagic dysfunction [36].…”
Section: Blockage Of P2x7r Activated Autophagic Ux In the Tncmentioning
confidence: 99%
“…Autophagy is regulated by immune signals [31]. Numerous studies have indicated the critical role of P2 × 7R in autophagy regulation [32][33][34][35][36][37]. The P2 × 7R-mediated autophagy modulation has been con rmed to participate in the pathophysiological process of amyotrophic lateral sclerosis [36], Duchenne muscular dystrophy [37] and status epilepticus [35].…”
Section: Introductionmentioning
confidence: 99%